Construção de um dispositivo que realiza todas as etapas do processo de sincronismo de um gerador a rede elétrica utilizando a plataforma de prototipagem eletrônica arduino - LIMA, Leonardo Brito (2018)
This final project on electrical engineering has the goal of contribute to the studying of the synchronism levels of synchronous electrical power systems. In addition, we developed a prototype to synchronize a generator connected to the electricity distribution network, which uses algorithms created to regulate and display subsystems, such as tension levels, lag tension, and frequency. This project was created using the knowledge obtained in the electrical engineering major, especially the control systems course, which taught us dada regulation using information obtained from the electric circuit created. Studying the results obtained from the electric circuit and from simulation on a signal generator, we concluded that the prototype is very close to a standard generator. Our system works with in the international regulation to synchronize an electrical generator with the electricity distribution network. Analyzing of the output signals and the control system was made using algorithms created to the Arduino prototyping platform, which utilizes a microcontroller board based on Atmel SAM3X8E ARM Cortex-M3 CPU (Arduino Due).